Prospective Pilot Study Comparing the Need for Adaptive Radiotherapy in Unresected Bulky Disease and in Postoperative Patients With Head and Neck Cancer. (December 2017) - Mahmoud, Omar; Reis, Isildinha M.; Samuels, Michael M.; Elsayyad, Nagy; Bossart, Elizabeth; Both, Joseph; ELGhoneimy, Ehsan; Moustafa, Magda; AbdAllah, Mohamed; Takita, Cristiane
Background: Adaptive radiotherapy is being used in few institutions in patients with head and neck cancer having bulky disease using periodic computed tomography imaging accounting for volumetric changes in tumor volume and/or weight loss. Limited data are available on ART in the postoperative setting. We aim to identify parameters that would predict the need for ART in patients with head and neck cancer and whether ART should be applied in postoperative setting. Materials and Methods: Twenty patients with stage III–IV head and neck cancer were prospectively accrued. A computed tomography simulation was done prior to treatment and repeated at weeks 3 and 6 of concurrent intensity-modulated radiotherapy and chemotherapy. The final plan was coregistered with the subsequent computed tomography images, and dosimetric/volumetric changes at weeks 1 (baseline), 3, and 6 were quantified in high-risk clinical target volumes, low-risk clinical target volumes, right parotid, left parotid, and spinal cord . An event to trigger ART was defined as spinal cord maximum dose >45 Gy, parotid mean dose >26 Gy, and clinical target volume coverage <95%. Results: Comparing the 2 groups, the proportion of patients with at least 1 event triggering ART was higher in bulky disease than in postoperative group: 72.7% versus 18.2% ( P = .03) overall; 54.6% versus 1.8% ( P = .064) at week 3; and 63.6% versus 18.2% ( P = .081) at week 6. In the bulky disease group, 8 of 11 patients had events at week 3 and/or 6 as follows: overdose in spinal cord (n = 2), right parotid (n = 3), left parotid (n = 5), coverage < 95% seen in low-risk clinical target volumes (n = 3), and high-risk clinical target volumes (n = 5). In the postoperative group, 2 of 11 patients had events: spinal cord (n = 1) and low-risk clinical target volume (n = 1). Conclusion: Our study confirmed the need for ART in patients with head and neck cancer having bulky disease due to target under dosing and/or spinal cord/parotids overdosing in weeks 3 and 6. In contrast, the benefit of ART in postoperative patients is less clear.